Report on the side-effects of Pharmacopuncture Lubricants(CF, JsD) - Jong Young, Lee; Hyun Min, Kang; Chung San, Lim; Ki Rok, Kwon (Korean Pharmacopuncture Institute, 2007)
Objectives : This study aims to report inflammatory reactions of Pharmacopuncture lubricants (CF and JsD) when administered on GB21, GB20, and TE23 in clinical trials. Methods : Follow-up studies were made on each patient's clinical observation and specific managemen. Results : 1. Inflammation induced by pharmacopuncture lubricants were limited to local area of administration. 2. Intensity of inflammation was depended on the patient's condition. 3. Inflammation caused pain, skin flare, and discomfort on the patient. Inflammation subsided when dissipating technique was rendered with the conventional acupuncture needle. Conclusions : It appears that prolonged usage of pharmacopuncture lubricant on the specific point can induce inflammation, thus using alternative pharmacopuncture is recommended.